Evaluation of Macronutrient Intake of a Group of Multiple Sclerosis Patients in Jordan - Mraish, Jamila H.; Takruri, Hamed R. (Pakistan Journal of Nutrition, 2016)
This study aimed at: evaluation of macronutrient intake and some of the anthropometric measurements (weight, height) and BMI (Body mass index) in a group of multiple sclerosis (MS) patients in Jordan. The study sample consisted of 60 subjects (47 females, 13 males), aged between 20-50 years, who attend the National Multiple Sclerosis Beta-Interferon Committee. A three-day food record was also used to collect dietary intake data. The studied sample was divided into three age groups: group 1: 20-29 years (n = 29), group 2: 30-39 years (n = 18) and group 3: 40-50 years (n = 13). The mean weight of the patients was 66.63 kg, mean height was 164.04 cm and mean BMI was 24.71. Sixty percent of the subjects had normal weight, whereas 5% had underweight status. Energy and carbohydrate intake of the whole sample was 90% of recommended values. The intake of total polyunsaturated fatty acids, omega-3 and omega-6 were inadequate (42.2, 44.7 and 45.9% of DRI, respectively). It could be concluded that multiple sclerosis patients in Jordan generally have adequate macronutrient intakes, but inadequate intake of essential fatty acids. No significant differences could be found between sample age groups. However, both anthropometric and nutritional variables of the patients were affected by gender.